2019
DOI: 10.1177/0361198119843099
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Effectiveness of Objective and Subjective Predictors of Driving Behavior under Fatigue

Abstract: There is growing evidence that driver fatigue is a major road safety problem, causing crashes that frequently involve fatalities and severe injuries. Professional drivers are among the road users indicated by literature to be at high risk of involvement in a fatigue-related crash. The goal of this paper is to investigate the effectiveness of objective and subjective data collection and analysis in predicting driving behavior under fatigue. Toward this goal, the impact of a fatigue-training program addressing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…e research in the field experiments found that the drowsy driving state generally lasted 15-75 seconds, while the typical drowsy operation characteristics duration was generally 5-20 seconds [30]. When measurements are calculated by data in the entire drowsy state duration, the calculating average effect covers the drowsy operating characteristics [1,18]. us, the doublelayer sliding time window was proposed to divide raw data into samples and calculate measurements.…”
Section: Setting Double-layer Sliding Time Window and Calculating Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…e research in the field experiments found that the drowsy driving state generally lasted 15-75 seconds, while the typical drowsy operation characteristics duration was generally 5-20 seconds [30]. When measurements are calculated by data in the entire drowsy state duration, the calculating average effect covers the drowsy operating characteristics [1,18]. us, the doublelayer sliding time window was proposed to divide raw data into samples and calculate measurements.…”
Section: Setting Double-layer Sliding Time Window and Calculating Measurementsmentioning
confidence: 99%
“…Drowsy driving is a typically dangerous driving behavior, which seriously threatens traffic safety and causes substantial financial costs to individuals and society [1][2][3]. Drowsy driving is a common phenomenon that results from multiple underlying reasons, including prolonged driving hours and sleep deprivation [3,4].…”
Section: Introductionmentioning
confidence: 99%